Analysing the ‘Black Box’ of HRM: Uncovering HR Goals, Mediators, and Outcomes in a Standardized Service Environment - Boxall, Peter; Ang, Siah Hwee; Bartram, Timothy (Journal of Management Studies, 2011)
abstract This multi‐level study analyses the ‘black box’ of HRM in an Australian cinema chain, a standardized service environment. Management's espoused goals for the casual workers who run the cinema service include attempts to build customer‐oriented behaviour, both directly and via empowerment, and also efforts to ensure compliance with company policies and to enhance employee commitment. Our analysis of an employee survey and supervisory performance ratings shows that it is behavioural compliance that is positively associated with rated performance rather than customer‐oriented behaviour. While customer service is an important value, it is willing engagement with a highly scripted, efficiency‐oriented work process that makes it happen, not a more empowering form of work design. On the other hand, the management process also fosters a level of employee commitment, which has some value in a tight labour market. The study demonstrates the way in which actual models of HRM can contain a complex and ‘contradictory’ set of messages, consistent with critical accounts of the labour process and suggesting that notions of ‘internal fit’ need to recognize such tensions. It underlines the importance of identifying the multiple goals in management's espoused theories of HRM and then assessing their links via managerial behaviour and employee responses to performance outcomes.